«YOLO – you only live once»: - Berit Johnsen; Vidar Skogvoll; Tom Normann (Nordisk Tidsskrift for Kriminalvidenskab)
Abstract This article presents a study of Norwegian prisoners’ experiences with anabolic-androgenic steroids (AAS) and other drugs. An intervention »Ren trening« was conducted by Antidoping Norge2 in the fall of 2019. Fieldwork was carried out at two drug treatment units with a total of 25 prisoners, 11 of which were interviewed. A bottom-up approach to the analyses of the data resulted in rich narratives that give a unique insight into prisoner experiences with AAS. Further analyses showed extensive use of AAS in combination with other narcotics, especially amphetamine. According to a typology developed by Christiansen et al. (2017), the uncritical use of AAS, without any consideration for its potentially serious side effects, can be understood as »YOLO – You Only Live Once«. Ambivalence surrounding the use of AAS, even if respect for clean exercise without the use of AAS is high, can be linked to pleasant experiences with these drugs. The body remembers these experiences and prisoners recall them with nostalgic undertones. The seriousness of the problems associated with the use of AAS, including criminal activity, indicates the importance of addressing these issues in prison.